2015
DOI: 10.1099/jgv.0.000291
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cellular prion protein in exosomes derived from ovine plasma

Abstract: Prion protein (PrP) is present at extremely low levels in the blood of animals and its detection is complicated by the poor sensitivity of current standard methodologies. Interesting results have been obtained with recent advanced technologies that are able to detect minute amounts of the pathological PrP (PrPSc), but their efficiency is reduced by various factors present in blood. In this study, we were able to extract cellular PrP (PrPC) from plasma-derived exosomes by a simple, fast method without the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In addition, IFNT induces ISG15 gene expression in jugular blood and liver tissue and several ISGs including ISG15, STAT1, and STAT2 in CL via uterine veins [ 43 , 44 ]. It has been reported that blood also contains exosomes for organ-to-organ communications [ 45 , 46 ]. Results from our studies together with these observations suggest that exosomes including IFNT could be involved in the regulation of ISGs in extra-uterine tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IFNT induces ISG15 gene expression in jugular blood and liver tissue and several ISGs including ISG15, STAT1, and STAT2 in CL via uterine veins [ 43 , 44 ]. It has been reported that blood also contains exosomes for organ-to-organ communications [ 45 , 46 ]. Results from our studies together with these observations suggest that exosomes including IFNT could be involved in the regulation of ISGs in extra-uterine tissues as well.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it is likely that conceptus secretes not only IFNT itself, but also IFNT incorporated into EVs, both of which act on the uterine endometrium, respectively. It is well documented that blood contains EVs for organ-to-organ communications [ 72 , 73 ]. Recently, extrauterine or endocrine effects of IFNT have also been noted [ 74 , 75 ], suggesting that EVs including IFNT could directly or indirectly function on extrauterine tissues as well.…”
Section: Roles Of Ev Interaction With Progesterone Ifnt and Lipimentioning
confidence: 99%
“…For example, EVs delivering pathological prions could affect normal cells and EVs carrying miR-29b could impede the neuroprotective function in HIV patients (Hu et al, 2012; Berrone et al, 2015; Caruso Bavisotto et al, 2019). Cellular prion protein (PrPC) from plasma-derived EVs might contribute to the pathogenesis and propagation of prion diseases such as transmissible spongiform encephalopathies (TSEs), a type of neurodegenerative disease (Berrone et al, 2015; Properzi et al, 2015b). The study by Nonaka et al (2013) reported TAR DNA-binding protein 43 (TDP-43) aggregates to be potentially conveyed from one cell to the other, to some extent, via EVs.…”
Section: Prospective Role Of Evs In Sci Treatmentmentioning
confidence: 99%